Mechanism of water-logging tolerance in pigeonpea - Hingane, A. J.; Saxena, K.B.; Patil, S.B.; Sultana, R.; Srikanth, S.; Mallikarjuna, N.; Vijakumar, R.; Kumar, C.V. Sameer (The Indian Journal of Genetics and Plant Breeding, 2016)
A study was undertaken to identify the morphophysiological traits associated with water-logging tolerance in pigeonpea [Cajanus cajan L. (Millsp.)].The formation of aerenchyma cells, lenticels, and adventitious roots in the tolerant genotypes were found to be associated with waterlogging tolerance in pigeonpea. The tolerant genotypes, namely, ICP 5028, ICPH 2431, ICPL 87119, ICPH 2740, ICPL 149, ICPL 20241, and MAL15, exhibited varying responses to hypoxic conditions. Formation of aerenchymatous cells was common in all the water-logging tolerant genotypes. Besides this, five tolerant genotypes (ICP 5028, ICPH 2431, ICPL 87119, ICPH 2740 and MAL 15) developed lenticels, while ICPL 149 and ICPL 20241 formed prominent adventitious roots. None of these traits was present in the susceptible genotypes.These traits developed only when exposed to water-logging stress and facilitated oxygen supply from stem to roots helping in respiration of the suffering plants. Potential breeding strategies to develop pigeonpea genotypes with enhanced levels of waterlogging tolerance are discussed.